2009
DOI: 10.1353/rhe.0.0068
|View full text |Cite
|
Sign up to set email alerts
|

Undocumented College Students, Taxation, and Financial Aid: A Technical Note

Abstract: A surprising amount of litigation and legislation has erupted over undocumented college students. Victims at the federal level are the DREAM Act and immigration reform. Financial aid raises technical issues for undocumented college applicants and for the citizen children of undocumented parents. Generally, the undocumented are ineligible for federal financial aid and nearly always for state aid. Even citizen college applicants face technical and administrative problems in negotiating the complex financial aid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 1 publication
0
47
0
Order By: Relevance
“…These students seldom have the necessary social and financial capital and overall support and guidance that can help them access and succeed in college (Baum & Flores, 2011;Teranishi et al, 2015). Limited access to state and federal financial aid coupled with the socioeconomic concerns, undocumented status, and high tuition prices cited above, leave many undocumented students without fruitful alternatives (Chin & Juhn, 2010;Olivas, 2009a). Additionally, studies have shown that the losses that arise as a result of bans on in-state tuition benefits are not limited to these students or their families.…”
Section: Literature On College Student Price Responsementioning
confidence: 99%
See 4 more Smart Citations
“…These students seldom have the necessary social and financial capital and overall support and guidance that can help them access and succeed in college (Baum & Flores, 2011;Teranishi et al, 2015). Limited access to state and federal financial aid coupled with the socioeconomic concerns, undocumented status, and high tuition prices cited above, leave many undocumented students without fruitful alternatives (Chin & Juhn, 2010;Olivas, 2009a). Additionally, studies have shown that the losses that arise as a result of bans on in-state tuition benefits are not limited to these students or their families.…”
Section: Literature On College Student Price Responsementioning
confidence: 99%
“…In addition, since undocumented students are considered non-residents, once the number of nonresident students exceed 10% of the State University System student population, undocumented students may be required to pay the higher non-resident tuition rate (NCSL, 2014b). While limited, both of these examples seemingly provide evidence that the issue of undocumented students' access to higher education is slowly coming to occupy a central place in public policy discussions (Dougherty et al, 2010), especially because, as pointed out by Olivas (2009a), "both advocates and opponents have targeted this issue as an important line in the sand" (p. 413). This notion is supported by evidence from the NILC (2014b) which indicates that, as of late 2014, at least 19 states were considering legislation related to either augmenting existing laws or adding new ones regarding undocumented student access and in-state tuition benefits including, for example, Connecticut (S.B.…”
Section: Policies On In-state Tuition For Undocumented Studentsmentioning
confidence: 99%
See 3 more Smart Citations